Student Resilience Concerning Discrepancies Between AcademicExpectations And Reality At Selected Universities - Yelsa Amanda; Reno Diqqi Alghzali; Regi Malsya; Dete Konggoro (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
The disparity between students’ initial expectations and the realities of college life may cause emotional stress, academic perplexity, and psychological adaptation problems. The complex reality of campus life often does not meet the idealistic image many students have of their academic accomplishments, the learning environment, and social interactions when they arrive at university. This state makes understanding academic resilience vital as the process of students adapting to the challenges of higher education. The purpose of this research is to analyze student resilience in the context of the gap between expectations of study and the reality of the university experience. This study combines a qualitative technique using a narrative inquiry research design. The participants were recruited purposively, consisting of three students from Sungai Penuh, Jambi, who continued their studies beyond their home region and had faced a mismatch between academic expectations and reality on campus. Data were acquired via in-depth semi-structured interviews and analyzed using thematic-reflective analysis. The research results demonstrate that the mismatch of expectations causes a phase of emotional disorientation characterized by disappointment, academic pressure, and a drop in self-confidence. However, individuals gradually built resilience through cognitive reframing, coping techniques, social support, emotional regulation, and reinterpretation of their academic experiences. This paper views academic resilience as a dynamic and ongoing adaptive process, rather than merely the ability to withstand pressure. This research underlines the necessity of psychological counseling services, counseling, and social assistance in higher education for students to acquire better skills in academic adaptation.